Methodological evaluation of leisure-time physical activity interventions in adults with obesity: a systematic review - Marina Christofoletti; Anne Ribeiro Streb; Robert Passos da Silva; Tânia Rosane Bertoldo Benedetti; Fábio Araújo Almeida; Giovani Firpo Del Duca (Revista Brasileira de Atividade Física e Saúde)
The aim of the present study was to systematize and analyze the methodological quality of physical activity interventions in leisure time in obese adults. A systematic review was conducted between June and August 2017 through four electronic databases (PubMed, Lilacs, ScienceDirect and Web of Science). A total of two researchers selected articles and, through consensus, analyzed these articles using the RE-AIM framework, which aims to identify the following dimensions: reach, effectiveness, adoption, implementation and maintenance of interventions. Of the 2,334 articles selected, nine met all eligibility criteria. The mean duration of the interventions was 14 weeks, with strategies including mainly aerobic exercises and nutritional monitoring. When the individual studies were taken into consideration, 67% reported at least one category of each dimension. The dimension with the highest reported proportion was “reach”, found in 65% of the interventions. The “effectiveness”, “adoption” (organizational and staff), “implementation” and “maintenance” dimensions (individual and organizational) were reported in less than 40% of the items investigated for this information. The conclusion is that most of intervention studies reported the “reach” dimension, while only a few described “maintenance”. Thus, it is suggested that future studies should previously look at the presentation of the total effect of the intervention and the methods applied, offering detailed information about each procedure. The scientific and practical scenario will provide relevant information about construction, application and subsequent follow-up of the interventions in leisure-time physical activity for obese adults.